Cyclic deformation of aluminium alloys after the preliminary combined loading. (November 2016) - Hutsaylyuk, Volodymyr; Snieżek, Lucjan; Chausov, Mykola; Torzewski, Janusz; Pylypenko, Andrii; Wachowski, Marcin
Abstract: This work explores sensitivity aluminium alloys under the influence of preliminary combined loading. There were examined 2024-T351 and D16ChATV aluminium alloys. The research was carried out under the conditions of tensile static and constant-amplitude fatigue tests on samples made of virgin material and after pre-combined loading. As a result of the research, it was concluded that the pre-combined loading leads to the modification of the mechanical properties of the tested materials. During the study reached similar results in increased strength for two aluminium alloys after the pre-combined loading, despite some differences in the structure of the output. Highlights: Combined pre-load of alloys 2024-T351 and D16ChATV leads to an abnormal plasticity. Plasticity depends on the type of realization of dynamic non-equilibrium processes. A new dissipative structure of the material does not relax after unloading. Virgin structure at a different load affects the formation of dissipative structures.